A BOLD Perspective on Age-Related Neurometabolic-Flow Coupling and Neural Efficiency Changes in Human Visual Cortex - Hutchison, Joanna L.; Shokri-Kojori, Ehsan; Lu, Hanzhang; Rypma, Bart (Frontiers in Psychology, 2013)
Age-related performance declines in visual tasks have been attributed to reductions in processing efficiency. The neural basis of these declines has been explored by comparing the blood-oxygen-level-dependent (BOLD) index of neural activity in older and younger adults during visual task performance. However, neural activity is one of many factors that change with age and lead to BOLD signal differences. We investigated the origin of age-related BOLD changes by comparing blood-flow and oxygen-metabolic constituents of BOLD signal. Subjects periodically viewed flickering annuli and pressed a button when detecting luminance changes in a central fixation cross. Using magnetic resonance dual-echo arterial spin labeling and CO2 ingestion, we observed age-equivalent (i.e., similar in older and younger groups) fractional cerebral blood flow (∆CBF) in the presence of age-related increases in fractional cerebral metabolic rate of oxygen (∆CMRO2). Reductions in ∆CBF responsiveness to increased ∆CMRO2 in elderly led to paradoxical age-related BOLD decreases. Age-related ∆CBF/∆CMRO2 ratio decreases were associated with reaction times, suggesting that age-related slowing resulted from less efficient neural activity. We hypothesized that reduced vascular responsiveness to neural metabolic demand would lead to a reduction in ∆CBF/∆CMRO2. A simulation of BOLD relative to ∆CMRO2 for lower and higher neurometabolic-flow coupling ratios (approximating those for old and young, respectively) indicated less BOLD signal change in old than young in relatively lower CMRO2 ranges, as well as greater BOLD signal change in young compared to old in relatively higher CMRO2 ranges. These results suggest that age-comparative studies relying on BOLD signal might be misinterpreted, as age-related BOLD changes do not merely reflect neural activity changes. Age-related declines in neurometabolic-flow coupling might lead to neural efficiency reductions that can adversely affect visual task performance.